Preparation and Properties of Cassava Starch-based Wood Adhesives - Qing Xu; Jianping Wen; Zhenjiong Wang (BioResources, 2016)
A biodegradable, environmentally friendly starch-based wood adhesive with cassava starch as a raw material and butyl acrylate (BA) as a co-monomer was synthesized. Results revealed that this cassava starch-based wood adhesive (SWA) was more stable than corn starch-based wood adhesive, and its bonding performance was close to that of commercial PVAc emulsion, even after 90 days of storage. Further analysis found that the improved stability of the adhesive could be attributed to its low minimum film forming temperature (MFFT) and glass transition temperature (Tg) of cassava starch. Moreover, the amount of total volatile organic compounds (TVOCs) emitted by the cassava starch-based wood adhesive were much lower than the Chinese national standard control criteria. Therefore, cassava SWA might be a potential alternative to traditional petrochemical-based wood adhesives.